Statistical Population Register: using administrative in the Canadian Census - Cloutier, Sylvain (International Journal of Population Data Science, 2018)
Introduction For a number of years, Statistics Canada has been evaluating the potential of increasing its use of administrative data into its Census Program. The research conducted so far has revealed that it could be possible to produce the census population counts by using existing administrative data. Objectives and Approach The building of the Statistical Population Register (SPR) is one step towards achieving the use of administrative data into the Canadian Census Program. In addition, the SPR, in combination with the Business Register and the Statistical Building Register, would support a more efficient production of statistics via a multi-register-based system in the future. The SPR is created by linking numerous administrative data sources (federal, provincial, municipal and private). The in-scope Canadian population is then identified and extracted from the SPR. Results The presentation will focus on the reasons as well as the goals that had to be met in the initial research project in order to demonstrate the potential of using administrative data within the Census Program. The current state of the project will be highlighted by presenting high-level results at the Canadian, provincial and territorial levels. This is accomplished by comparing the Statistical Population Register’s in-scope population to its reference, Statistics Canada’s official population counts. Conclusion/Implications Despite promising results, areas of improvements have already been identified and work is under way in order to improve the quality of the upcoming Statistical Population Register. The final section of the presentation will be devoted to the future research agenda of the Census Program.